Oral malignant melanoma: A silent killer? - Ashvini Padhye; Jovita D'souza (Wolters Kluwer Medknow Publications, 2011)
Oral malignant melanomas are extremely rare lesions and occur commonly in the maxillary gingiva more frequently on the palate with fewer incidences in the mandibular gingiva. Though these lesions are biologically aggressive, they often go unnoticed since they are clinically asymptomatic in the early stages and usually present merely as a hyperpigmented patch on the gingival surface. These lesions if diagnosed at an early in situ stage are potentially curable and definitely have a better prognosis, but unfortunately as they are clinically asymptomatic, it results in delayed diagnosis thus making the prognosis extremely poor. This paper presents the case of a patient who visited our department with the complaint of darkened patches on the gums and his concern was purely aesthetic. There were no symptoms associated with the hyperpigmented lesions and hence the patient did not approach us earlier. When the lesions grew larger and were unsightly, the patient has seeked dental advice. Histopathologic investigation confirmed the diagnosis as 'Oral Malignant Melanoma'. Though aggressive therapy was instilled immediately, unfortunately, the patient succumbed to death within a few months after diagnosis as the lesion was highly invasive. Due to the biologically aggressive but clinically silent nature of progression of the lesion, the importance of maintaining a high index of suspicion and early detection and diagnosis for any pigmented gingival lesions cannot be overemphasised. Diagnosis must be based on thorough detailed history and valid histologic evidence.